Efisiensi Teknis Usaha Tani Padi Organik Lahan Sawah Tadah Hujan di Kabupaten Tanggamus Provinsi Lampung - Ktut Murniati; Jangkung Handoyo Mulyo; Irham Irham; Slamet Hartono (Politeknik Negeri Lampung., 2014)
Research on technical efficiency of organic rice farming was conducted in Tampang Tua Vallage, Pematang Sawa District,Tanggamus Regency, Lampung Province. by using the respondents were 60 people taken by the census of the entire organic rice farmers. The aim of this research to analyze technical efficiency, factors influencing technical efficiency, and source of technical inefficiency of rainfed farm organic rice. Technical efficiency is measured by using frontier production function and is istimated using MLE method with Frontier 4.1c computer program. Estimation source of technical inefficiency applies linear regression model that approach simultaneously using frontier production function. The research result indicates that most variables are significant and have expected signs, except for organik solid feltilizer has not significant. The research olso find that the level of technical efficiency varies from 0.423 to 0.999 with the average of 836. Furthermore, variables of farmers education levels, farm organic rice experience, age of the farmers, frekuency of farmers agricultural extentions, and farmer perception on climate change are influencing to reduce technical inefficiency. Keywords: technical efficiency, organic rice, and rainfed paddy field